Optimisme Karier dalam Menghadapi Perkembangan AI: Studi Fenomenologis tentang Human Touch pada Jurnalis Media Digital - Iffah Hidayatur Rohmah; Diana Rahmasari; Hermien Laksmiwati (Varied Knowledge Journal, 2026)
The development of Artificial Intelligence (AI) has transformed digital journalistic practices, particularly in information searching, transcription, data processing, and news draft preparation. This transformation raises questions about the sustainability of the journalism profession amid the increasing automation of work. This study aims to explore how journalists construct career optimism in the AI era and how human touch is interpreted as a source of confidence in the sustainability of the journalism profession. This study employed a qualitative approach using interpretative phenomenology. Data were collected through semi-structured interviews with eight digital journalists and analyzed using thematic analysis. Data trustworthiness was strengthened through member checking. The findings revealed three main themes: AI as a work partner that supports technical tasks while still requiring human control; human touch as a professional advantage that also strengthens journalists’ professional identity; and journalists’ authority in maintaining information credibility. These findings indicate that journalists’ career optimism is not naive; rather, it is formed through critical adaptation, the reinforcement of professional identity, and the interpretation of human values in journalistic practice.